2008
DOI: 10.1111/j.1469-0691.2008.01986.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA microarray-based genotyping of methicillin-resistant Staphylococcus aureus strains from Eastern Saxony

Abstract: A diagnostic microarray was used to characterise a collection of methicillin-resistant Staphylococcus aureus (MRSA) isolates from hospitals in the German region of Eastern Saxony. The most abundant epidemic MRSA (EMRSA) strains were ST5-MRSA II (Rhine-Hesse EMRSA, EMRSA-3), CC5/ST228-MRSA I (South German EMRSA), ST22-MRSA IV (Barnim EMRSA, EMRSA-15) and ST45-MRSA IV (Berlin EMRSA). Other strains were found only as sporadic isolates or in minor outbreaks. These strains included ST1-MRSA IV, ST8-MRSA IV (Hannove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
182
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(185 citation statements)
references
References 36 publications
3
182
0
Order By: Relevance
“…A recent study from Australia suggested that in all strains a similar repertoire of virulence gene exist pointed out that these genetic elements might serve as candidates for a DNA chip based typing system similar to that for St. aureus [21]. In summary, our current results are encouraging.…”
Section: Resultssupporting
confidence: 56%
“…A recent study from Australia suggested that in all strains a similar repertoire of virulence gene exist pointed out that these genetic elements might serve as candidates for a DNA chip based typing system similar to that for St. aureus [21]. In summary, our current results are encouraging.…”
Section: Resultssupporting
confidence: 56%
“…Isolates (collected in routine diagnostics) from 126 consecutive SAB patients hospitalized in 2006 -2007 at Akershus University Hospital, Lørenskog, Norway, were genotyped as described earlier (6,7). The complete microarray hybridization data are provided in the supplemental material.…”
mentioning
confidence: 99%
“…All MRSA isolates associated with the cluster were investigated by DNA microarray analysis using the StaphyType kit (Alere Technologies GmbH, Jena, Germany) to detect 334 S. aureus gene sequences and alleles, including antimicrobial resistance genes, virulence-associated genes, and typing markers (23). The array also assigned isolates to a multilocus sequence type (ST) and/or clonal complex (CC) and SCCmec type (25).…”
Section: Methodsmentioning
confidence: 99%